ANALISIS KEMAMPUAN LITERASI MATEMATIS PADA MATERI BANGUN DATAR DENGAN MEDIA BATIK BETAWI MOTIF TUMPAL - Vyvy Hindun Permatasari; Meyta Dwi Kurniasih (KALAMATIKA Jurnal Pendidikan Matematika, 2021)
Batik Betawi is one of the elements of Betawi culture heritage that needs to be reserved. This element of Betawi culture can be used as a learning and teaching media since it has patterns correlated to mathematics. One of the patterns that can be used as a mathematics lesson at school is the batik Betawi tumpal pattern, formed by triangles and squares. This research aims to examine the role of Betawi culture in mathematical literacy. This research implements the qualitative descriptive method with ethnographic approach. The results show that batik Betawi tumpal has a significant effect on mathematical literacy and it is also applicable to the teaching of plane geometry. Batik Betawi tumpal pattern as one of the elements of Betawi culture is relevant to use as a teaching media of plane geometry. It can also be used as a tool to visualize the object in concrete form to be more comprehensible for the students.